The Effectiveness of Herbal Medicines on Cyclic Mastalgia: A Systematic Review on Meta-analysis - Mirzaee, Firoozeh; Fakari, Farzaneh Rashidi; Babakhanian, Masoudeh; Roozbeh, Nasibeh; Ghazanfarpour, Masumeh (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Objective Different drugs are used to treat mastalgia, such as danazol and bromocriptine, and both are associated with side effects, due to which most of women and healthcare providers are interested in herbal medicines. Therefore we aim to study the effectiveness of phytoestrogens on the severity of cyclic mastalgia.Methods To carry out the present study, English electronic resources such as the Cochrane Library, ISI Web of Science, Scopus, and PubMed were used systematically and with no time limitation up to February 10, 2020.Results In total, 20 studies were included in the present meta-analysis. The results of the meta-analysis showed that herbal medicines versus the control group (standard mean difference [SMD] = - 0.585; 95% confidence interval [CI]: - 0.728–- 0.44; heterogeneity; p = 0.02; I2 = 42%), herbal medicines versus the B group (SMD = - 0.59; 95%CI: - 0.75–- 0.44; heterogeneity; p = 0.03; I2 = 42%), and its subgroups, such as phytoestrogen (SMD = - 0.691; 95%CI: - 0.82–- 0.55; heterogeneity; p = 0.669; I2 = 0%), Vitex-agnus-castus (SMD = - 0.642; 95%CI: - 0.84–- 0.44; p < 0.001; p = 203; I2 = 32%), flaxseed (SMD = - 0.63; 95%CI: - 0.901–- 0.367; p = 0.871; I2 = 0%), and evening primrose (SMD= - 0.485; 95%CI:- 0.84–- 0.12; p = 0.008; heterogeneity; p = 0.06; I2 = 56%] may have effective and helpful effects on improving cyclic breast mastalgia. Also, chamomile, isoflavone, cinnamon, and nigella sativa significantly reduced mastalgia symptoms.Conclusion Herbal medicines and their subgroups may have effective and helpful effects on improving cyclic breast mastalgia. The findings of our meta-analysis must be done cautiously because low methodological quality in some evaluated studies of this systematic review.
Keywords: mastodynia; phytoestrogens; systematic review; herbal medicine